2012
DOI: 10.9753/icce.v33.currents.27
|View full text |Cite
|
Sign up to set email alerts
|

Non-Hydrostatic Modelling of Infragravity Waves Using Swash

Abstract: This paper presents numerical modelling of the nearshore transformation of infragravity waves induced by bichromatic wave groups over a horizontal and a sloping bottom. The non-hydrostatic model SWASH is assessed by comparing model predictions with analytical solutions over a horizontal bottom and with detailed laboratory observations for a sloping bottom. Good agreement between model predictions and data is found throughout the domain for bound infragravity waves. Furthermore the model predicts greater outgoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 15 publications
1
9
0
2
Order By: Relevance
“…Second-order bound infragravity waves are added at the offshore boundary so that the wave field is consistent with the non-linear momentum equations. For a more in-depth description of the model, see Zijlema et al (2011), Rijnsdorp et al (2012) and Smit et al (2013). We ran the model in profile (onedimensional, 1D) mode for 3 monotonic sloping beaches (β¼ 1:80, 1:40 and 1:20), starting in 20-m water depth.…”
Section: Discussionmentioning
confidence: 99%
“…Second-order bound infragravity waves are added at the offshore boundary so that the wave field is consistent with the non-linear momentum equations. For a more in-depth description of the model, see Zijlema et al (2011), Rijnsdorp et al (2012) and Smit et al (2013). We ran the model in profile (onedimensional, 1D) mode for 3 monotonic sloping beaches (β¼ 1:80, 1:40 and 1:20), starting in 20-m water depth.…”
Section: Discussionmentioning
confidence: 99%
“…We use the numerical model SWASH to simulate the transformation of nearshore wavefields over variable profiles. SWASH is a nonhydrostatic model based on the nonlinear shallow water equations [ Zijlema et al ., ] and has shown to accurately capture the nearshore processes of breaking [ Smit et al ., ], infragravity wave dynamics [ Rijnsdorp et al ., ], run‐up oscillations [ Ruju et al ., ] and nonlinear wave dynamics [ Smit et al ., ].…”
Section: Methodsmentioning
confidence: 99%
“…We use the numerical model SWASH to simulate the transformation of nearshore wavefields over variable profiles. SWASH is a nonhydrostatic model based on the nonlinear shallow water equations [Zijlema et al, 2011] and has shown to accurately capture the nearshore processes of breaking [Smit et al, 2013], infragravity wave dynamics [Rijnsdorp et al, 2012[Rijnsdorp et al, , 2015, run-up oscillations [Ruju et al, 2014] and nonlinear wave dynamics [Smit et al, 2014]. Because the SWASH model will be used here to study wave propagation in a cross-shore/one-dimensional setting, the governing equations can be written as @g @t 1 @ @x ð g 2d udz50;…”
Section: Numerical Modelmentioning
confidence: 99%
“…However, one is refer to Zijlema and Stelling (2005) and Zijlema et al (2011) for details. Also, details on the imposition of the boundary conditions can be found in Zijlema et al (2011) and Rijnsdorp et al (2012).…”
Section: Swash: a Non-hydrostatic Wave-flow Modelmentioning
confidence: 99%
“…This model is an open source tool developed at Delft University of Technology (http://swash.sf.net) and it was demonstrated to be capable to model low frequency waves and the subsequent hydrodynamic processes in the sandy coast environment (see, e.g. Zijlema et al 2011;Rijnsdorp et al 2012). In this study, the validity of SWASH in describing wave transformation across fringing reefs and reproducing the interaction between low frequency waves and the reef will be examined.…”
Section: Introductionmentioning
confidence: 99%